Target Detection Using Fused Unidentical Photonics-Based LFM Sub-Band Radar Signals With an Adaptive Feed Forward Network Equalizer - Bikash Nakarmi; S. M. Rezwanul Islam; Hum Nath Parajuli; Ikechi Augustine Ukaegbu; Aigerim Ashimbayeva; Carlo Molardi; T. D. Subash; Xiangchuan Wang; Shilong Pan (IEEE Access)
To address the challenges of costly frontend high frequency opto-electronics devices and the requirement of high bandwidth for improved range, resolution several band fusion techniques are proposed in this work. However, conventional band fusion techniques fuse the bands with identical bandwidth and same chirp rates. This paper proposes and experimentally demonstrates sub-bands fusion of photonically generated linear frequency modulated (Ph-LFM) radar signals with unidentical bandwidth and chirp rates using an adaptive, delay-less feed-forward network equalizer (FFNE). We demonstrate this using optical injection in a semiconductor laser to generate Ph-LFM signals at different IEEE X-KA radar sub-bands: 19.25–23.94 GHz and 24.06–28.31 GHz (bandgap 0.12 GHz), 19.69–23.06 GHz and 23.625–27 GHz (bandgap 0.56 GHz), and 8–11.5 GHz and 12.75–17 GHz (bandgap 1.25 GHz). Time-frequency analysis (TFA) was used to obtain sub-bandgap signals of 0.12 GHz, 0.56 GHz, and 1.25 GHz which are coherently fused using the FFNE with a particle swarm optimization (PSO) algorithm to optimize complex-valued weights. The method is evaluated by measuring the range resolution and peak-to-sidelobe level (PSL) in detecting two objects separated by 2 cm and 3 cm. The FFNE achieves significant improvement over 10 dB in PSL and resolves previously unresolvable distances, with maximum range resolutions of 1.8 cm, 2.2 cm, and 2 cm, closely matching theoretical values for full-band LFM signals with bandwidth of 9.06 GHz, 7.31 GHz, and 9 GHz, respectively. Experimental results demonstrate the FFNE’s superior performance in enhancing range resolution and PSL in multi-sub-band radar systems compared to scenarios without FFNE.